2022
DOI: 10.1155/2022/7535215
|View full text |Cite
|
Sign up to set email alerts
|

Research on Optimization of Large Flow Hydraulic Punching Process in Zhaozhuang Mine

Abstract: Taking hydraulic punching test of Zhaozhuang Mine as engineering background, by comparing the field application effects of different hydraulic punching processes, the relationship between coal moisture content around the borehole blockage and gas extraction effect was monitored and analyzed. The following conclusions were drawn: the occurrence of borehole blockage was the result of the comprehensive action of coal slag particle size and slag discharge capacity of punching return water. Blocking the borehole le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Xu 52 and other scholars, on the other hand, used a combination of field tests and numerical simulations to analyze and study the effects of different coal output and different mining periods on the effective mining radius, using Zhong Macun coal mine as an example, and the increase in coal production can improve the effective mining radius of the borehole. In the hydraulic punching test in Zhaozhuang mine, Zhang 53 and other scholars compared the field application effects of different hydraulic punching processes, monitored and analyzed the relationship between the water content of coal around the borehole blockage and the gas extraction effect, and concluded that the occurrence of borehole blockage was the result of the combined effect of cinder particle size and punching back water discharge capacity.…”
Section: Current Status Of Research On Hydraulic Coal and Gas Outburs...mentioning
confidence: 99%
“…Xu 52 and other scholars, on the other hand, used a combination of field tests and numerical simulations to analyze and study the effects of different coal output and different mining periods on the effective mining radius, using Zhong Macun coal mine as an example, and the increase in coal production can improve the effective mining radius of the borehole. In the hydraulic punching test in Zhaozhuang mine, Zhang 53 and other scholars compared the field application effects of different hydraulic punching processes, monitored and analyzed the relationship between the water content of coal around the borehole blockage and the gas extraction effect, and concluded that the occurrence of borehole blockage was the result of the combined effect of cinder particle size and punching back water discharge capacity.…”
Section: Current Status Of Research On Hydraulic Coal and Gas Outburs...mentioning
confidence: 99%